Anseios de um pensar crítico: tensões entre ensaio e poesia em Paulo Leminski - Kühn, Ana Érica Reis da Silva (2018)
The present thesis, Yearnings of a critical thinking: tensions between essays and poetry within Paulo Leminski, analyses the essays of this poet from Curitiba, its critic and poetry. We aim, from this scope, to map and analyze the tensions that occur in these productions. As a way to understand if they constitute a contradiction in Leminski’s speech, as well as if they bring “metamorphoses” to his poetic work. This study is divided into three moments, the first, in which we seek to place Leminski in a tradition of Brazilian critic-poets, such as Mario de Andrade and the triad of the concretists poets, formed by Augusto and Haroldo de Campos and Décio Pignatari. In addition to that we carried a survey on the collection of essays from the author that were published in national circulation newspapers, in magazines known as “nanicas”, besides the books organized by the author himself, by his heirs or by publishers. In the second moment, we built some considerations towards the essay genre, rescuing its origins from the French essayist Montaigne, as a way to understand why Leminski had chosen to develop his critic through the essay and not another genre. We understand that the essay, considered a hybrid genre par excellence, enabled the author to dialogue with other forms and discourses. In a way that his essay development ended up being extended to his creative work, originating a reflexive expression that culminated in poems-critics and into poetics essays, corresponding to the epistles that Leminski sent to friends as a way to discuss the ideas surrounding his inventive process. In the third moment, we turned ourselves to investigate the dialogue that the author established with his predecessors, from whom we chose three components that we consider to be fundamental to the modeling of his diction, the Concretism, the countercultural “várzea” and the haicai. It interested us to debate what Leminski says in his critic towards these aesthetics, once his statements, sometimes, diverge from what he performed in his poetry. The analyses carried out show that the essay production is guided by tensions. These are related to his yearning for the reader and also to the precepts that guide the traditions chosen by the poet to guide his expression. Because what he demonstrates to acknowledge about them is not what he applies in his own poetry. Moreover, we verified that Leminski’s relation with his predecessors is also guided by the veil of denial and misreading, aspects that contributed for the poet to forge a poetical diction that was not permanently affiliated to any aesthetic.